Increased Serum Aminotransferase Activity and Clinical Outcomes in Coronavirus Disease 2019 - Ramachandran, Preethi (J Clin Exp Hepatol, 2020)
AIM: Elevation of hepatic aminotransferases (aspartate aminotransferase [AST]/alanine aminotransferase [ALT]) is commonly noted among COVID-19 patients. It is unclear if they can predict the clinical outcomes among hospitalized COVID-19 patients. We aim to assess if elevations in AST/ALT were associated with poor outcomes in hospitalized COVID-19 patients. METHODS: We retrospectively evaluated hospitalized COVID-19 patients with clinically significant elevated aminotransferases (defined as >2 times upper limit of normal) and compared them with COVID-19 patients without an elevation in aminotransferases. RESULTS: The prevalence of elevation in AST/ALT was found to be 13.7% (20/145). The two groups were similar in baseline demographics, comorbidities, and the majority of laboratory tests. There was no difference in the mortality (50% vs. 36.8%, P = 0.32) and median hospital stay (7 days vs. 7 days, P = 0.78). However, there was a statistically significant increase in the rates of mechanical ventilation among elevated aminotransferases group compared with individuals without elevation (50% vs. 24%, P = 0.028). However, this difference was not observed after adjusting for inflammatory markers such as ferritin, lactate dehydrogenase, and lactic acid levels. CONCLUSION: Elevated aminotransferases among hospitalized COVID-19 patients is associated with higher rates of mechanical ventilation but did not achieve statistical significance after controlling for inflammatory markers. Also, patients with elevated aminotransferases did not have higher rates of mortality or prolonged length of stay.